White packaging adhesive film with high volume resistance, preparation method of white packaging adhesive film and photovoltaic module
By modifying titanium dioxide and blending it with EVA resin, a high volume resistance white packaging film was prepared, which solved the problems of low volume resistivity and high water vapor transmission rate of white EVA film, significantly reduced the PID phenomenon of solar cells and improved the aging resistance of the film.
Patent Information
- Application Number
- CN202510122280.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-04-25
AI Technical Summary
The low volume resistivity and high water vapor transmission rate of the white EVA film lead to potential-induced attenuation (PID) phenomenon in high temperature and high humidity environments, affecting the power output of the battery.
A high volume resistance white encapsulation film was prepared by modifying titanium dioxide, adding crosslinked silane and blending with insulating nanomaterials and EVA resin. The method includes heating and dissolving titanium dioxide in an ethanol solution, adding crosslinked silane for reflux reaction, then mixing with insulating nanomaterial and EVA resin, extrusion granulation and lamination curing, to obtain a white encapsulated film with high volume resistance.
The volume resistivity and crosslinking degree of the adhesive film are improved, the water vapor transmission rate is reduced, the migration of metal ions is effectively suppressed, the PID phenomenon of solar cells is reduced, and the storage and service life of the adhesive film is extended.
Smart Images

Figure CN119875534A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of packaging adhesive films, and in particular relates to a white packaging adhesive film with high volume resistance, a preparation method thereof, and a photovoltaic module. Background Art
[0002] The main function of photovoltaic encapsulation film is to encapsulate the solar cell between the upper and lower layers of glass or between glass and a plastic backplane, and to form a photovoltaic power generation module with a frame around it. When the solar cell encounters a high temperature and high humidity environment during the actual power generation process of a power station, the metal ions in the upper and lower surface glass will migrate to the surface of the solar cell through the adhesive film, causing the solar cell power attenuation phenomenon. This phenomenon is called potential induced degradation (PID attenuation for short). The laboratory simulated outdoor losses under -1500V voltage and double 85 aging conditions and found that some power attenuation reached 20%, causing great power loss. The actual application experience in the industry has proved that improving the volume resistivity and water vapor barrier of EVA encapsulation film can effectively prevent the migration of metal ions and reduce the PID phenomenon of solar cells.
[0003] In addition, the titanium dioxide filler in the white EVA film has strong water absorption due to the presence of water-absorbing functional groups such as hydroxyl groups on its surface. As the storage time increases, it is very easy to absorb water and cause the hydrolysis of the silane additive in the film, which in turn causes the white EVA film packaging to have insufficient adhesion, seriously restricting the storage and use of the white film. The addition of titanium dioxide also further deepens the disadvantage of insufficient volume resistivity after aging.
[0004] Therefore, how to overcome the low volume resistivity defect of white EVA film is a technical problem that needs to be solved urgently in this field.
[0005] It should be noted that the above information disclosed in this background technology section is only used to understand the background technology of the present application concept, and therefore, the above description is not considered to constitute information of the prior art. Summary of the invention
[0006] The embodiments of the present disclosure at least provide a white packaging adhesive film with high volume resistance, a preparation method thereof, and a photovoltaic module.
[0007] In a first aspect, an embodiment of the present disclosure provides a white packaging film with high volume resistivity and a preparation method thereof, comprising the following steps: step S1, modifying titanium dioxide, namely heating the titanium dioxide in an ethanol solution to 50-70°C and stirring for 1-2h until dissolved, then adding cross-linking silane, mixing evenly and reflux reacting at 70-90°C, filtering, washing, and drying, and drying at 120-140°C to obtain modified titanium dioxide; step S2, preparing titanium dioxide masterbatch, namely uniformly mixing the modified titanium dioxide, insulating nanomaterial and matrix resin, extruding and granulating at 80-120°C to obtain titanium dioxide masterbatch; step S3, preparing a white packaging film, namely blending the titanium dioxide masterbatch with EVA resin, adding an initiator, a co-crosslinking agent, a light stabilizer, an antioxidant, a silane coupling agent and a superhydrophobic silane and uniformly mixing, and after absorption, casting, embossing, cooling and winding through a screw extruder to obtain a white packaging film.
[0008] In an alternative embodiment, the cross-linking silane comprises at least one isocyanate group and at least one silane group.
[0009] In an optional embodiment, the cross-linking silane includes any one or more combinations of 3-isocyanatepropyltrimethoxysilane, α-isocyanatemethyltrimethoxysilane, α-isocyanatemethyldimethoxysilane, α-isocyanatemethyltriethoxysilane, γ-isocyanatepropyltrimethoxysilane, γ-isocyanatepropyltriethoxysilane, 3-isocyanatepropyltriethoxysilane, isocyanatepropylmethyldimethoxysilane, isocyanatepropyldimethylmethoxysilane, isocyanatepropylmethyldiethoxysilane, trimethylsilyl isocyanate and 3-isocyanatepropyldiethoxysilane.
[0010] In an optional embodiment, the white packaging film in step S2 comprises the following components in parts by mass: 10-50 parts of modified titanium dioxide, 1-10 parts of insulating nanomaterials, and 40-89 parts of base resin.
[0011] In an optional embodiment, the insulating nanomaterial includes any one or more combinations of zirconium oxide, magnesium oxide, boron nitride, mica, aluminum oxide, zinc oxide, aluminum fluoride, silicon oxide, silicon nitride and magnesium nitride.
[0012] In an optional embodiment, the super hydrophobic silane includes any one or more combinations of n-octyltriethoxysilane, n-octyltrimethoxysilane, n-hexyltrimethoxysilane, n-decyltrimethoxysilane, hexadecyltrimethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, octyltrimethoxysilane oligomer, octyltriethoxysilane oligomer, tridecafluorooctyltrimethoxysilane, tridecafluorooctyltriethoxysilane, heptadecafluorodecyltrimethoxysilane and octadecyltrimethoxysilane.
[0013] In a second aspect, the embodiments of the present disclosure further provide a white packaging adhesive film with high volume resistance, which is prepared by the method described above; the cross-linking degree of the white packaging adhesive film is 75-90%.
[0014] In an optional embodiment, the volume resistivity of the white packaging film is 5.0*10 14 ~9.0*10 15 .
[0015] In an optional embodiment, the water vapor permeability of the white packaging film is 25-33 g / m 2 / day.
[0016] In a third aspect, the embodiments of the present disclosure further provide a photovoltaic module, which uses the white packaging film with high volume resistance as described above.
[0017] The beneficial effects of the present invention are that, under the premise of not changing the melt index of the resin, the white packaging film with high volume resistance and its preparation method and the photovoltaic module select a cross-linked silane coupling agent to carry out surface coating modification on the existing titanium dioxide powder, and by introducing cross-linking functional groups on the surface, a cross-linking reaction of the titanium dioxide powder is achieved during the lamination process, thereby improving the cross-linking degree of the film, thereby improving the volume resistance of the film and reducing the PID phenomenon of the solar cell.
[0018] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention are realized and obtained by the structures particularly pointed out in the description and the drawings.
[0019] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 This is an infrared test image of a modified titanium dioxide provided in an embodiment of the present disclosure. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] As used herein, the phrases "in one embodiment," "according to one embodiment," "in some embodiments," and the like generally refer to the fact that the particular feature, structure, or characteristic following the phrase may be included in at least one embodiment of the present disclosure. Therefore, a particular feature, structure, or characteristic may be included in more than one embodiment of the present disclosure, so that these phrases do not necessarily refer to the same embodiment. As used herein, the terms "example," "exemplary," and the like are used to "serve as an example, instance, or illustration." Any implementation, aspect, or design described herein as "example" or "exemplary" is not necessarily to be construed as preferred or superior to other implementations, aspects, or designs. On the contrary, the use of the terms "example," "exemplary," and the like is intended to present concepts in a concrete manner.
[0024] Herein, example embodiments of the present disclosure will be described in more detail with reference to the accompanying drawings. As used herein, expressions such as "at least one of..." modify the entire list of elements when following a list of elements, rather than modifying individual elements in the list. For example, the expression "at least one of a, b, and c" should be understood to include only a, only b, only c, both a and b, both a and c, both b and c, or all of a, b, and c.
[0025] The terms used herein are only used to describe specific exemplary configurations and are not intended to be limited. As used herein, the singular articles "one", "an" and "the" may also be intended to include plural forms, unless it is clearly indicated above that this is not the case. The terms "comprise", "include" and "have" are inclusive, and therefore specify the presence of features, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, elements, components and / or combinations thereof. The method steps, processes and operations described herein should not be interpreted as necessarily requiring them to be performed in the specific order discussed or shown, unless specifically identified as an execution order. Additional or alternative steps may be adopted.
[0026] To address the issues of low volume resistivity and high water vapor permeability of the film, currently disclosed patents mainly adopt the solution of using low VA resin and a second resin.
[0027] Patent CN117210143A discloses a high-resistance, low-cost encapsulation film preparation solution, which improves the film's resistance and aging adhesion by adding double-bond olefin oligomers to the existing film system.
[0028] Patent CN118027824A discloses an EVA film for solar cell encapsulation with high volume resistivity and high water vapor barrier and a preparation method thereof. By selecting an EVA resin with a high melting point and ultra-low VA (vinyl acetate structural unit): the content of the vinyl acetate structural unit is 6wt.% to 19wt.%, and introducing some modified petroleum resin, it is possible to use EVA resin raw materials with low vinyl acetate content and high melting point to prepare an EVA encapsulation film with higher volume resistivity and water vapor barrier.
[0029] However, double-bond olefin oligomers and petroleum resins have poor film-forming properties and poor compatibility with EVA resins. Cast extrusion can easily cause crystal point breakage problems. At the same time, this type of resin has poor antioxidant properties, and long-term use of components can easily cause yellowing and corrosion problems.
[0030] At the same time, although the use of high melting point ultra-low VA (vinyl acetate structural unit) can increase the overall volume resistance of the film, low VA resin generally has a high melting point, the resin is hard, and it is difficult to process. The film lamination is prone to cause battery cell cracking. During the processing, the peroxide cross-linked EVA resin is prone to premature cross-linking and curing due to excessive temperature, resulting in difficulty in extrusion or even inability to extrude.
[0031] The defects existing in the above solutions are the results obtained by the inventor after practice and careful research. Therefore, the discovery process of the above problems and the solutions proposed by the present disclosure for the above problems below should be the contributions made by the inventor to the present disclosure during the disclosure process.
[0032] Some embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0033] The embodiment of the present disclosure provides a white packaging film with high volume resistivity and a preparation method thereof, comprising the following steps: step S1, modifying titanium dioxide, namely heating titanium dioxide in an ethanol solution to 50-70° C. and stirring for 1-2 hours until dissolved, then adding cross-linking silane, mixing evenly and reflux reaction at 70-90° C., and drying at 120-140° C. after suction filtration, washing, and drying to obtain modified titanium dioxide; step S2, preparing titanium dioxide masterbatch, namely uniformly mixing modified titanium dioxide, insulating nanomaterials, and matrix resin, extruding and granulating at 80-120° C. to obtain titanium dioxide masterbatch; step S3, preparing white packaging film, namely blending titanium dioxide masterbatch with EVA resin, adding initiator, auxiliary cross-linking agent, light stabilizer, antioxidant, silane coupling agent, and superhydrophobic silane and uniformly mixing, and after absorption, casting, embossing, cooling, and winding by a screw extruder to obtain a white packaging film.
[0034] In some embodiments, specifically, the cross-linking silane contains at least one isocyanate group and at least one silane group, and isocyanate silane is selected as a modifier so that the surface of the titanium dioxide contains both isocyanate groups (--N=C=O) and silane groups (Si-R). The grafted silane group is more stable than the added silane coupling agent, is resistant to hydrolysis, and has stable adhesion, thereby ensuring that the film has good adhesion during long-term storage.
[0035] In some embodiments, specifically, the cross-linking silane includes any one or more combinations of 3-isocyanate propyl trimethoxy silane, α-isocyanate methyl trimethoxy silane, α-isocyanate methyl dimethoxy silane, α-isocyanate methyl triethoxy silane, γ-isocyanate propyl trimethoxy silane, γ-isocyanate propyl triethoxy silane, 3-isocyanate propyl triethoxy silane, isocyanate propyl methyl dimethoxy silane, isocyanate propyl dimethyl methoxy silane, isocyanate propyl methyl diethoxy silane, trimethylsilyl isocyanate and 3-isocyanate propyl diethoxy silane.
[0036] In some embodiments, specifically, the white packaging film in step S2 comprises the following components by mass: 10-50 parts of modified titanium dioxide, 1-10 parts of insulating nanomaterials, and 40-89 parts of base resin.
[0037] In some embodiments, specifically, the insulating nanomaterial includes any one or more combinations of zirconium oxide, magnesium oxide, boron nitride, mica, aluminum oxide, zinc oxide, aluminum fluoride, silicon oxide, silicon nitride and magnesium nitride, and a new insulating nanomaterial is introduced into the masterbatch. On the one hand, the nano-insulating material has excellent thermal conductivity and insulation performance at high temperature, which improves the volume resistance of the film. At the same time, the nanopore size of the insulating material has excellent adsorption performance and aging resistance, which can adsorb the free ions generated by the film and glass during the aging process, thereby improving the aging resistance of the component.
[0038] In some embodiments, specifically, the super hydrophobic silane includes any one or more combinations of n-octyltriethoxysilane, n-octyltrimethoxysilane, n-hexyltrimethoxysilane, n-decyltrimethoxysilane, hexadecyltrimethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, octyltrimethoxysilane oligomer, octyltriethoxysilane oligomer, tridecafluorooctyltrimethoxysilane, tridecafluorooctyltriethoxysilane, heptadecafluorodecyltrimethoxysilane and octadecyltrimethoxysilane. A new long-chain hydrophobic silane is introduced into the existing formula system. Compared with the existing silane coupling agent, the long-chain silane has more stable performance, contains hydrophobic functional groups on the surface, and is more hydrophobic. It can effectively reduce the water vapor permeability of the film, thereby improving the water vapor aging resistance of the component.
[0039] The disclosed embodiment also provides a white packaging film with high volume resistance, which is prepared by the above-mentioned method; the cross-linking degree of the white packaging film is 75-90%.
[0040] In some embodiments, specifically, the volume resistivity of the white packaging film is 5.0*10 14 ~9.0*10 15 .
[0041] In some embodiments, specifically, the water vapor permeability of the white packaging film is 25 to 33 g / m 2 / day.
[0042] The disclosed embodiment also provides a photovoltaic module, which adopts the white packaging film with high volume resistance as mentioned above.
[0043] Example 1
[0044] A white packaging film with high volume resistance and a preparation method thereof, comprising the following steps:
[0045] Step S1, modifying titanium dioxide, namely, heating 10 parts of titanium dioxide in an ethanol solution to 70° C. and stirring for 1 hour until dissolved, then adding 0.04 parts of cross-linking silane 3-isocyanate propyltrimethoxysilane, mixing evenly and reflux reaction at 90° C., filtering, washing, drying and drying at 120° C. to obtain modified titanium dioxide;
[0046] See also Figure 1 ,like Figure 1 As shown in the figure, it can be seen that the modified titanium dioxide after calcination is better than the initial titanium dioxide in the range of 1200-1300cm -1 The CN stretching vibration peak belonging to cross-linked silane appears in the wavelength range, proving that silane is successfully coated on the surface of titanium dioxide.
[0047] Step S2, preparing titanium dioxide masterbatch, that is, uniformly mixing 10 parts of modified titanium dioxide, 5 parts of insulating nanomaterial silicon nitride and 85 parts of commercially available 2825EVA resin as a matrix resin, and extruding and granulating at 80-120° C. to obtain titanium dioxide masterbatch;
[0048] Step S3, preparing a white encapsulating film, that is, blending 10 parts of titanium dioxide masterbatch with 90 parts of EVA resin, adding 0.05 parts of initiator TBEC, 0.05 parts of co-crosslinking agent TAIC, 0.01 parts of light stabilizer UV770, 0.01 parts of antioxidant 1010, 0.04 parts of silane coupling agent KH570 and 0.04 parts of superhydrophobic silane hexadecyltrimethoxysilane and evenly mixing, and after absorption is completed, casting, embossing, cooling and winding through a screw extruder to obtain a white encapsulating film.
[0049] According to the method of Example 1, Examples 1-11 were prepared, and the component ratios and performance data are shown in Table 1 below.
[0050] Table 1
[0051]
[0052]
[0053]
[0054] Performance testing method:
[0055] Water vapor transmission rate test method: Reference national standard: GB / T1027-2008;
[0056] The test methods for crosslinking degree and volume resistivity refer to the industry standard: T / CPIA0073-2024.
[0057] Reflectivity test method:
[0058] a. Pressed part preparation: prepare 2 pieces of 30mm×30mm PET release films;
[0059] b. Release film → packaging film → release film are stacked in sequence;
[0060] c. Place the film in a laminator and perform curing and cross-linking according to the curing temperature and time required by the encapsulation film product to obtain a laminate without appearance defects, and the degree of cross-linking of the encapsulation film after lamination should reach more than 80%;
[0061] d. Place the laminated assembly in a UV-Vis spectrophotometer to test the average reflectivity of 400-1100 nm.
[0062] PID attenuation test reference standard: IEC61215-2:2021.
[0063] Specifically, as shown in Example 9, titanium dioxide that has not been surface-coated with a silane coupling agent is prone to hydrolysis, resulting in power attenuation.
[0064] Specifically, as shown in Example 10, when superhydrophobic silane is not added to the resin, the water vapor permeability of the white film is significantly increased, and the power attenuation is significant.
[0065] In summary, the present white encapsulation film with high volume resistance and its preparation method, and the photovoltaic module select a cross-linked silane coupling agent to carry out surface coating modification on the existing titanium dioxide without changing the melt index of the resin. By introducing cross-linking functional groups on the surface, the cross-linking reaction of titanium dioxide is realized during the lamination process, the cross-linking degree of the film is improved, and then the volume resistance of the film is improved, thereby reducing the PID phenomenon of the solar cell.
[0066] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing a white packaging film with high volume resistance, characterized in that: The steps include: Step S1, modifying titanium dioxide, That is, titanium dioxide is heated to 50-70°C in an ethanol solution and stirred for 1-2 hours until dissolved, then cross-linking silane is added, mixed evenly, and refluxed at 70-90°C for reaction, filtered, washed, dried, and then dried at 120-140°C to obtain modified titanium dioxide; Step S2, preparing titanium dioxide masterbatch, That is, the modified titanium dioxide, insulating nanomaterials and matrix resin are uniformly mixed, extruded and granulated at 80-120°C to obtain titanium dioxide masterbatch; Step S3, preparing a white packaging film, That is, titanium dioxide masterbatch is blended with EVA resin, and initiator, co-crosslinking agent, light stabilizer, antioxidant, silane coupling agent and superhydrophobic silane are added and evenly mixed. After absorption, the white packaging film is obtained by casting, embossing, cooling and winding through a screw extruder.
2. The preparation method according to claim 1, characterized in that The crosslinking silane comprises at least one isocyanate group and at least one silane group.
3. The preparation method according to claim 2, characterized in that: The cross-linking silane includes any one or more combinations of 3-isocyanate propyl trimethoxy silane, α-isocyanate methyl trimethoxy silane, α-isocyanate methyl dimethoxy silane, α-isocyanate methyl triethoxy silane, γ-isocyanate propyl trimethoxy silane, γ-isocyanate propyl triethoxy silane, 3-isocyanate propyl triethoxy silane, isocyanate propyl methyl dimethoxy silane, isocyanate propyl dimethyl methoxy silane, isocyanate propyl methyl diethoxy silane, trimethylsilyl isocyanate and 3-isocyanate propyl diethoxy silane.
4. The preparation method according to claim 1, characterized in that: The white packaging film in step S2 comprises the following components in parts by mass: 10-50 parts of modified titanium dioxide, 1-10 parts of insulating nanomaterials, and 40-89 parts of base resin.
5. The preparation method according to claim 1, characterized in that: The insulating nanomaterial includes any one or more combinations of zirconium oxide, magnesium oxide, boron nitride, mica, aluminum oxide, zinc oxide, aluminum fluoride, silicon oxide, silicon nitride and magnesium nitride.
6. The preparation method according to claim 1, characterized in that: The super hydrophobic silane includes any one or more combinations of n-octyltriethoxysilane, n-octyltrimethoxysilane, n-hexyltrimethoxysilane, n-decyltrimethoxysilane, hexadecyltrimethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, octyltrimethoxysilane oligomer, octyltriethoxysilane oligomer, tridecafluorooctyltrimethoxysilane, tridecafluorooctyltriethoxysilane, heptadecafluorodecyltrimethoxysilane and octadecyltrimethoxysilane.
7. A white packaging film with high volume resistance, characterized in that: Prepared by the method according to any one of claims 1 to 6; The cross-linking degree of the white packaging film is 75-90%.
8. The white packaging film with high volume resistance as claimed in claim 7, characterized in that: The volume resistivity of the white packaging film is 5.0*10 14 ~9.0*10 15 .
9. The white packaging film with high volume resistance as claimed in claim 7, characterized in that: The water vapor permeability of the white packaging film is 25-33 g / m 2 / day.
10. A photovoltaic module, characterized in that: A white packaging film with high volume resistance as described in any one of claims 7 to 9 is used.